Effectiveness of Indirect Decompression in Severe Degenerative Lumbar Central Canal Stenosis by Oblique Lumbar Interbody Fusion - Sharvil Gajjar; Amit Jhala; Manish Mistry (Journal of Minimally Invasive Spine Surgery and Technique, 2021)
Objective To evaluate the efficacy of indirect decompression achieved by Oblique Lumbar Interbody Fusion in severe degenerative lumbar central canal stenosis in Schizas grade C and D according to pre-operative MRI and whether direct decompression was a necessity in such cases. The efficacy of indirect decompression is established for mild to moderate stenosis with instability. But insufficient data are available regarding its feasibility in Schizas grade C and D stenosis. Methods OLIF was carried out in 37 patients/44 segments, which fell into the category of Schizas grade C or D were included in the study. Clinical assessment was done using modified Macnab criteria. Percentage improvement in foraminal height, disc height, segmental lordosis, spinal canal area, and reduction in listhesis were measured. Patients were followed up for a period of a minimum of 1 year. Statistical analysis was done by Wilcoxon signed Ranks test, paired T-test, and Chi-square test. Results Clinically good to excellent result was achieved by OLIF in 94.59%. Radiologically, the average improvement in foraminal height was by 20.06%, disc height by 86.01%, segmental lordosis by 3.8° listhesis reduction by 51.8%, and spinal canal area by 75.36%. None required direct posterior decompression. Conclusion Indirect decompression is effective in Schizas grade C and D stenosis with early excellent to good results clinically. There is improvement in disc height, foraminal height, segmental lordosis, and overall spinal canal area by OLIF (Study design: retrospective).